Simulation of a mini adsorber for cooling applications - Wong, Keith Wen Hui. (2013)
This report presents the thermodynamic modelling and simulation of a miniature adsorption cooler (MAC), which is developed from (i) experimentally confirmed silica gel (type RD) –water based adsorption isotherms and kinetics data, and (ii) the mass, and energy balances of all components of the cooler. Combining all mass and energy balances equations, the thermodynamic approach has been extended to quantify the performances of the MAC in terms of load surface temperatures and coefficient of performance (COP). The simulation provides a test-of-concept for the design, development and fabrication of the MAC. The proposed MAC fulfills the following aims: (1) scale independence; (2) nearly free of moving parts; (3) relatively high coefficient of performance; (4) sizable cooling densities; and (5) fabrication from non-toxic environmentally-friend materials. The size (cooling capacity) of this chiller can be miniaturised with an amplification of cooling efficiency. This insensitivity to scale creates promising applications in areas ranging from the cooling of personal computers and other microelectronics appliances, to conventional automotive and room air conditioning, and, possibly, cryomedical procedures.